2016
DOI: 10.1002/cmmi.1686
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effectiveness of transferrin receptor‐1 (TfR1) as a magnetic resonance reporter gene

Abstract: Magnetic resonance (MR) reporter genes have the potential for tracking the biodistribution and fate of cells in vivo, thus allowing the safety, efficacy and mechanisms of action of cell‐based therapies to be comprehensively assessed. In this study, we evaluate the effectiveness of the iron importer transferrin receptor‐1 (TfR1) as an MR reporter gene in the model cell line CHO‐K1. Overexpression of the TfR1 transgene led to a reduction in the levels of endogenous TfR1 mRNA, but to a 60‐fold increase in total T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 36 publications
2
21
1
Order By: Relevance
“…30 We have previously shown that overexpression of iron transporters such as TFR1 can lead to a decrease in the expression of endogenous transferrin receptors and an upregulation of ferritin expression. 31 In contrast to TFR1 overexpression, magA did not affect the expression of endogenous TFR1 , although we have seen a modest increase in FTH1 protein. Although it is tempting to suggest that this could be related to magA ’s function as an iron transporter, leading to more iron uptake and consequently an increase in FTH1 translation, recent evidence suggests that magA is not only unnecessary for magnetosome formation in MTBs but also unlikely to work as an iron transporter.…”
Section: Discussioncontrasting
confidence: 62%
“…30 We have previously shown that overexpression of iron transporters such as TFR1 can lead to a decrease in the expression of endogenous transferrin receptors and an upregulation of ferritin expression. 31 In contrast to TFR1 overexpression, magA did not affect the expression of endogenous TFR1 , although we have seen a modest increase in FTH1 protein. Although it is tempting to suggest that this could be related to magA ’s function as an iron transporter, leading to more iron uptake and consequently an increase in FTH1 translation, recent evidence suggests that magA is not only unnecessary for magnetosome formation in MTBs but also unlikely to work as an iron transporter.…”
Section: Discussioncontrasting
confidence: 62%
“…Due to surface effects and cation vacancies in its antiferromagnetic iron core, ferritin generates detectable T 2 ‐derived MR‐contrast . However, despite all efforts to further improve its relaxivity,[1c,2] ferritin still does not qualify as a robust gene reporter for MRI, mainly because of the limits imposed by its weakly magnetized ferrihydrite core. [1b]…”
Section: Introductionmentioning
confidence: 99%
“…Thus, approximately 10% of these nanoparticles can be seen in the macrophages and finally lead to misinterpretation of results related to the location and survival of therapeutic administered cells . Indirect labelling of the transplanted cells is implemented by the genetic manipulation via MRI reporter gene, but this method lacks sufficient sensitivity for the cell detection . MRI offers the best anatomical position of the cell graft but lacks adequate information about function, viability and behaviour of the transplanted cells …”
Section: Molecular Imagingmentioning
confidence: 99%
“…68 Longitudinal relaxation time agents (paramagnetic-based agents, implemented by the genetic manipulation via MRI reporter gene, but this method lacks sufficient sensitivity for the cell detection. 68,89 MRI offers the best anatomical position of the cell graft but lacks adequate information about function, viability and behaviour of the transplanted cells. 90…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%